Simulation and Entrustment in Cardiac Surgery - McEwen, Charlotte (My University, 2025)
This thesis explored how simulation can be leveraged to support the entrustment of high-acuity, low-opportunity (HALO) entrustable professional activities in cardiac surgery. Two paired studies were undertaken: a domain-specific replication study testing the use of one type of structured simulation, simulation-based mastery learning, for a HALO cardiac surgery skill, and a theory-informed qualitative study exploring the lived experiences of entrustment as it related to simulation training. Taken together, these studies provide a window into the interaction of simulation and entrustment in a Canadian subspecialty training program, and generate hypotheses about how simulation might be leveraged to address the challenge of entrustment for high risk and rare skills.
MANAGING RISK: EXPLORING HOW SIMULATION OF HIGH-ACUITY, LOW-OPPORTUNITY EVENTS CAN TRANSFER TO SAFE TRAINEE ENTRUSTMENT IN THE OPERATING ROOM
Keywords: Simulation; Education; Cardiac Surgery; Surgery; Simulation-Based Mastery Learning; Entrustment